A new approach for leptomeningeal metastases: chemotherapy administered through lumbar intrathecal port - Comlek, Savas; Saglam, Sezer (Arquivos de Neuro-Psiquiatria, 2021)
Background: Intrathecal chemotherapy is a local therapeutic modality used for treatment of leptomeningeal metastases. However, the techniques currently used, i.e. repeated lumbar puncture and Ommaya reservoir, have certain disadvantages. Lumbar intrathecal port (LIP) placement is a relatively novel technique, which has been used for pain management in cancer patients. Objective: To investigate the use of LIP for intrathecal administration of chemotherapeutic agents in patients with leptomeningeal metastases. Methods: Retrospective study of 13 patients treated with intrathecal chemotherapy for secondary leptomeningeal involvement of a primary solid tumor were included in this retrospective study. The patients received intrathecal chemotherapy through a LIP. Results: The patients received a total of 123 intrathecal chemotherapy doses. No grade 3-4 toxicity, technical problem or severe complication developed. During a median of 136 days of follow-up (range, 67-376 days), 12 patients died (92.3%). The treatment resulted in symptom improvement in all patients and self-rated overall health and quality of life improved, compared with baseline. Conclusions: The LIP system, which has been used for intrathecal pain management for decades, appears to offer a safe alternative for intrathecal chemotherapy in patients with leptomeningeal metastases. Further studies are warranted to clarify its potential use in this setting.
Keywords: Neoplasm Metastasis; Meningeal Carcinomatosis; Injections, Spinal; Drug Therapy; Spinal Puncture